Legal Analysis of Trading in the Digital Age: Weaknesses and Enforcement Efforts in Indonesia - Mulyadi, Dudi (PT. Anagata Sembagi Education, 2025)
The development of digital technology has driven significant transformation in the trade and investment sector in Indonesia, especially in online-based trading practices. The integration of high-speed internet, big data, and automated trading algorithms makes it easier to access global markets, improve transaction efficiency, and expand public participation. However, these advances also pose legal risks, such as market manipulation, insider trading, investment fraud, and personal data protection breaches. Normatively, the regulation has been accommodated through Law No. 8 of 1995 concerning the Capital Market, Law No. 11 of 2008 jo. Law No. 19 of 2016 concerning ITE, as well as OJK and Bappebti regulations. However, the regulation has not fully anticipated the complexity of the digital ecosystem which is real-time and cross-jurisdictional. Challenges include limited surveillance technology, weak intergovernmental coordination, and low legal and financial literacy of the community. This study uses normative juridical methods with legal and conceptual approaches to assess the suitability, weaknesses, and needs of legal reform. The results of the study emphasized the urgency of regulatory harmonization, strengthening RegTech and SupTech, establishing an integrated law enforcement model, and international cooperation. This effort is expected to be able to build a digital trading ecosystem that is safe, transparent, adaptive to innovation, and globally competitive.